2020
DOI: 10.1093/jxb/eraa386
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral function of the phytochelatin synthase C-terminal domain in inhibition of heavy metal-mediated enzyme overactivation

Abstract: Phytochelatin synthases (PCSs) play essential roles in detoxification of a broad range of heavy metals in plants and other organisms. Until now, however, no PCS gene from liverworts, the earliest branch of land plants and possibly the first one to acquire a PCS with a C-terminal domain, has been characterized. In this study, we isolated and functionally characterized the first PCS gene from a liverwort, Marchantia polymorpha (MpPCS). MpPCS is constitutively expressed in all organs examined, with stronger expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 80 publications
1
31
0
Order By: Relevance
“…Although it was thought for long time that bryophytes do not synthesize PCn under metal stress [ 55 , 57 , 100 , 101 , 102 ], Petraglia et al [ 103 ] demonstrated instead that constitutively expressed and functional PCSs are present in a number of bryophytes, as well as in other early-diverging streptophytes, arguing that the ability to synthesize PCn, as well as the presence of active PCSs, are ancestral (plesiomorphic) traits of early-diverging plants [ 103 ]. This study was followed by others, supporting the idea that PCn synthesis is an important mechanism of intracellular Cd detoxification, both in bryophytes, such as in L. riparium [ 62 ], L. cruciata [ 75 , 104 ], M. polymorpha [ 105 , 106 ], and in charophytes, such as N. mucronata [ 77 ]. In addition to the ability to synthesize PCn, vacuolar compartmentalization plays a key role in metal detoxification in bryophytes and charophytes, as well as in higher plants, as supported by the intravacuolar electron-dense Cd deposit detected in L. cruciata [ 75 ].…”
Section: Response To Cadmium Toxicity In Charophytes and Bryophytessupporting
confidence: 61%
“…Although it was thought for long time that bryophytes do not synthesize PCn under metal stress [ 55 , 57 , 100 , 101 , 102 ], Petraglia et al [ 103 ] demonstrated instead that constitutively expressed and functional PCSs are present in a number of bryophytes, as well as in other early-diverging streptophytes, arguing that the ability to synthesize PCn, as well as the presence of active PCSs, are ancestral (plesiomorphic) traits of early-diverging plants [ 103 ]. This study was followed by others, supporting the idea that PCn synthesis is an important mechanism of intracellular Cd detoxification, both in bryophytes, such as in L. riparium [ 62 ], L. cruciata [ 75 , 104 ], M. polymorpha [ 105 , 106 ], and in charophytes, such as N. mucronata [ 77 ]. In addition to the ability to synthesize PCn, vacuolar compartmentalization plays a key role in metal detoxification in bryophytes and charophytes, as well as in higher plants, as supported by the intravacuolar electron-dense Cd deposit detected in L. cruciata [ 75 ].…”
Section: Response To Cadmium Toxicity In Charophytes and Bryophytessupporting
confidence: 61%
“…For PCS, being rich in Cys is one of its important features. The C 358 C 359 XXXC 363 XXC 366 motif is a heavy metal sensor, which is capable of transferring heavy metal ions to the N-terminal catalytic region when they are detected (Vestergaard et al, 2008;Li et al, 2020 1A), which is identical to the motif in PcPCS1 and similar to that in LjPCS1. These results reveal that BnPCS1 has similar characteristics to the PCS homologs from the other diverse plant species, and may perform similar functions.…”
Section: Discussionmentioning
confidence: 99%
“…For PCS, being rich in Cys is one of its important features. The C 358 C 359 XXXC 363 XXC 366 motif is a heavy metal sensor, which is capable of transferring heavy metal ions to the N-terminal catalytic region when they are detected ( Vestergaard et al, 2008 ; Li et al, 2020 ). This motif appears as C 368 C 369 RETC 373 MKC 376 in LjPCS1 and C 369 C 370 QETC 374 VKC 377 in PcPCS1, while this motif is present as C 371 C 372 QETC 376 VKC 379 in BnPCS1 ( Figure 1A ), which is identical to the motif in PcPCS1 and similar to that in LjPCS1.…”
Section: Discussionmentioning
confidence: 99%
“…Such metal-selectivity of PCSs raises a significant question of how PCSs distinguish the activating ions and others. Recent studies from our group and others suggest that the different regions of the C-terminal regulatory domain of PCSs are involved in the metal(loid)-specific activation [16,[49][50][51][52].…”
Section: Preferential Interaction Between Phytochelatin and CDmentioning
confidence: 99%
“…Such metal-(loid) PCS activation mechanism has been a significant question. Recent studies suggest that the different regions of the C-terminal regulatory domain of PCSs are required for the metal(loid)-specific activation [17, [50][51][52][53],…”
Section: Preferential Interaction Between Phytochelatin and CDmentioning
confidence: 99%